New species of Ameletus Eaton, 1885 and redescription of Ameletus longulus Sinichenkova, 1981 from the Russian Far East (Ephemeroptera: Ameletidae) - Tiunova, Tatiana M. (Zootaxa, 2013)
Ameletus khasanensis sp. nov. is described and Ameletus longulus Sinichenkova, 1981 is revalidated and redescribed based on material from the Russian Far East. The structure of the penis of both species is similar to that of Ameletus costalis (Matsumura 1931), a description and drawings of which are also presented in this paper. The male imago of A. khasanensis sp. nov. can be distinguished from that of A. costalis by the absence of spinules on the dorsal surface of the fore tibia. The male imago of A. longulus can be distinguished from A. khasanensis sp. nov. and A. costalis by the color of the forewings. The larvae of A. khasanensis sp. nov. differ from A. costalis in the length of the denticles on the right mandible, in the absence of the group of setae on the dorsal surface at the base of fore femora and the width/length ratio of gillVII. The larvae of A. longulus differ from A. khasanensis and A. costalis in the form and number of the denticles of the first comb-shaped seta of the maxilla and the number of setae on the dorsal surface of the base of the fore femora.